ChemInform Abstract: Nickel‐Catalyzed Activation of Acyl C—O Bonds of Methyl Esters. Issue 26 (June 2016) - Hie, Liana; Fine Nathel, Noah F.; Hong, Xin; Yang, Yun‐Fang; Houk, Kendall N.; Garg, Neil K.
Abstract: It is established for the first time that the C—O bonds of simple esters can be activated using a distinct catalytic system.